Correlation of 75g oral glucose tolerance test (OGTT) values with pregnancy outcomes in a tertiary care unit - Jayarathna, R.N.; Wijeyaratne, C.N.; Dodampahala, S.H.; Lankeshwara, D.; Randeniya, R. (The Sri Lanka College of Obstetricians and Gynaecologists, 2007)
BACKGROUND Gestational diabetes mellitus (GDM) is a common problem in Sri Lankan tertiary care. Accurate diagnosis by OGTT is important. OBJECTIVE To assess the correlation of OGTT values with pregnancy management and outcome METHOD - DESIGN Retrospective observational study RESULTS 83 women screened by OGTT in mid trimester during 2007 were recruited postpartum. Of them 25 had normal and 36 had abnormal glucose tolerance (20 - frank diabetes; 16 impaired glucose tolerance (IGT)), WHO recommendations 1999; 22 others had 'unusual OGTT' -2 hour value >140 mg/dl and low 1 hour value. Mean age was 31.4 ñ 5.3 years. Median parity 2; mean number of children 1 with 17 primigravida. OGTT had been performed at average gestational age 23.2 ñ 6.7 weeks. Mean 1h and 2h OGTT values (mg/dl) were: normal -152.7 ñ 6.7 and 113 ñ 17.9, frank diabetes - 201ñ28.5 and 189ñ21.6, IGT - 179ñ22.6 and 149ñ11.4 and 'unusual OGTT' - 118.7ñ16.4 and 147ñ8.6 respectively. Maternal glycaemia by Blood Sugar Series at average gestational age 26.9ñ6.7 weeks - mean pre meal and mean 2 hour post meal blood glucose (mg/dl): normal - 96.8ñ11.4 and 101.9ñ17.2 and 'unusual OGTT 87.2ñ14.3 and 99.9ñ2 respectively. PREGNANCY OUTCOME 'Unusual OGTT'- none required insulin; 14 (63.6 percent) had vaginal delivery. 7 LSCS for previous section and one assisted delivery with mean birth weight 2767ñ471.5g Normal OGTT - 19 (76 percent) vaginal delivery and 6 (24 percent) LSCS, with mean birth weight 3039ñ516g Frank diabetes - 7 (35 percent) required insulin. Nine(45 percent) vaginal delivery, 10 (50 percent) LSCS and one vacuum -extraction with average birth weight 3134ñ 350.2 g (p<0.05) CONCLUSIONS Pregnant women with the 2nd hour value of OGTT higher than the 1st hour value have normal glycaemia requiring no intervention and have a pregnancy outcome similar to those with normal OGTT. RECOMMENDATIONS When diagnosing GDM in tertiary care practice it is best to study the 1st hour value of the OGTT in addition to the 2nd hour value before labeling a woman as having abnormal glucose tolerance.
Keywords: OGTT; TERTIARY CARE UNIT